Competition and Succession in Pastures 2001
DOI: 10.1079/9780851994413.0103
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and stability in humid temperate pastures.

Abstract: The hypothesis to be explored in the present chapter is that plant species diversity conveys stability - in time and space - to pasture performance. Due to environmental heterogeneity in both space and time, it is hypothesized that pasture stability will increase as plant species diversity increases up to an optimum that is greater than would be predicted from short-term, small-plot clipping trials. It is theorized that the simple mixtures commonly recommended today predispose swards to yield fluctuation, weed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The lack of any effect for grazing frequency or any interaction involving grazing frequency for combined DM yield, when there had been a year × grazing frequency × pasture interaction for legume DM yield (Fig. 1), suggested that mixture components were sufficiently complementary to overcome the effects of grazing frequency treatment every year and maintain a relatively stable level of production from year to year despite grazing treatments or environmental differences (Haynes, 1980; Sanderson and Elwinger, 2002). It also suggested that under both the grazing treatments imposed, KC/TF combined DM yield also was driven by the legume component, as was ALF/TF grazed every other month, similarly to the findings of Lauriault et al (2003) Combined DM yield of ALF/TF grazed every month and BFT/TF and CM/TF in both grazing treatments, however, was driven more by the grass component as it benefited from nitrogen (Edwards et al, 1996; Loiseau et al, 2001) supplied by an albeit lesser yield contribution from the legumes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of any effect for grazing frequency or any interaction involving grazing frequency for combined DM yield, when there had been a year × grazing frequency × pasture interaction for legume DM yield (Fig. 1), suggested that mixture components were sufficiently complementary to overcome the effects of grazing frequency treatment every year and maintain a relatively stable level of production from year to year despite grazing treatments or environmental differences (Haynes, 1980; Sanderson and Elwinger, 2002). It also suggested that under both the grazing treatments imposed, KC/TF combined DM yield also was driven by the legume component, as was ALF/TF grazed every other month, similarly to the findings of Lauriault et al (2003) Combined DM yield of ALF/TF grazed every month and BFT/TF and CM/TF in both grazing treatments, however, was driven more by the grass component as it benefited from nitrogen (Edwards et al, 1996; Loiseau et al, 2001) supplied by an albeit lesser yield contribution from the legumes.…”
Section: Resultsmentioning
confidence: 99%
“…R ECENTLY, there has been increased interest in maximizing utilization of irrigated pastures in the western USA because of changes in federal land policies on public grazing lands and the desire to reduce costs by using animals for harvesting (Asay et al, 2001;Guldan et al, 2000;Waldron et al, 2002). Many producers prefer monoculture grass pastures because they are easier to manage (Beuselinck et al, 1994;Clark, 2001). Maximum production by cool-season pasture grasses in the West is nearly impossible without irrigation (Waldron et al, 2002), but tall fescue is a high yielding perennial cool-season grass (Leep et al, 2002;Waldron et al, 2002) that is among the most stable in maintaining yield across varied irrigation levels (Lauriault et al, 2005b;Waldron et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Botanical composition was used to calculate the additive effect of each species, or the expected change in nutritive value associated with a change in proportion of a species in the mixture from 0 to 100%. These results have led some to conclude that the benefits of increased diversity are best realized in mixtures of relatively few species (two to four) selected for their adaptation to a particular environment (Clark, 2001;Tracy and Sanderson, 2004;Nyfeler et al, 2009). White clover and meadow fescue had a positive additive effect on forage digestibility (range of 36 to 80 g kg 1 ), but alfalfa and reed canarygrass had no additive effect on digestibility.…”
Section: Researchmentioning
confidence: 99%
“…Previous studies have shown contrasting effects of plant diversity on forage yield, ranging from positive effects [6–9] to no effects [10], or even negative effects [11]. A primary conclusion drawn from these contrasting results is that the effect of species diversity on forage production per se is not as important as that of certain plant functional groups and/or the combination of these functional groups [12], probably because functional trait diversity and composition in complex forage mixtures can be a strong driver of resource utilization and yield production [13]. …”
Section: Introductionmentioning
confidence: 99%